Growing edible mushrooms: a conversation between bacteria and fungi. (9th September 2019) - Carrasco, Jaime; Preston, Gail M.
Summary: Mushroom cropping consists of the development and fructification of different fungal species in soil or selective substrates that provide nutrients and support for the crop. The microorganisms present in these environments strongly influence, and in some cases are required for the growth and fructification of cultivated mushrooms. Some fungi such as truffles and morels form ectomycorrhizal associations with host plants. For these fungi, helper bacteria play an important role in the establishment of plant‐fungal symbioses. Selective processes acting on the microbiota present in substrates and soils determine the composition of the microbiota inhabiting the fruit bodies or interacting with fungal hyphae, and both configure the mushroom holobiont, understood as the fungus plus associated microorganisms. Here, we review current knowledge regarding the cross‐talk between bacteria and fungi during mushroom cultivation. We highlight the potential use of bioinoculants as agronomical amendments to increase mushroom productivity through growth promotion or as biocontrol agents to control pests and diseases.